Military ideology and culture of violence in school communities in the Amazon context - Lopes, Laio; Oliveira, Selma Suely Baçal de (Seven Editora, 2024)
This article presents a vision of the current project in the educational field called the Civic-Military Schools Program (PECIM) in the Legal Amazon (AL), taking as a reference the State's actions investing in shared management with the armed and auxiliary forces to serve schools classified as areas of social vulnerability. PECIM was implemented in 2020 and reached a significant number of school institutions on the national scene that decided to adopt the model. By the end of 2022, 49 schools were recorded in AL. The pedagogical conception that favors militarized indoctrination in areas considered to be socially vulnerable is an educational proposal from the national State that exposes political-ideological interests in the region. Document analysis was the proposal used to extract information from the legal documents that guide PECIM within a qualitative methodological approach to reference the historical milestones that contextualize the role of the National State in a critical-reflexive perspective on combating violence in school communities and the rise of the military narrative as a political educational project from a hegemonic perspective. The region, which lives with environmental crimes and the rise of organized crime, sees military participation expand its functions, establishing a power project with education as its pillar. DOI:https://doi.org/10.56238/sevened2024.009-014